Effect of sodium chloride on the seedlings of Cressa cretica L. - Balasubramanian1*, P. Amuthavalli1,; P. Sivaraman2, S. Sivasankaramoorthy1, T. (Journal of Ecobiotechnology, 2011)
<span style="font-size: 10pt; line-height: 110%; font-family: ";Garamond";,";serif";; mso-fareast-font-family: SimSun; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: ZH-CN; mso-bidi-language: AR-SA;">The effect of different concentrations of sodium chloride on growth and organic components of Cressa cretica, has been made. Cressa cretica, could survive a wide range of NaCl (0-400 mM) salinity. The upper limit for the survival of seedlings to NaCl salinity was 400 mM. However, optimal growth responses by the seedlings were confirmed to 200 mM NaCl. There was depressed growth in the absence of salt and at extreme salinity. Under NaCl salinity accumulation of ions and organic components such as starch and protein increased with increasing salt concentrations upto optimal level and decreased at higher concentration. On the otherhand, free amino acid and total sugar decreased with increasing concentrations of NaCl upto optimal level and increased at higher concentration. The proline content increased with increasing concentration upto the extreme level of NaCl salinity.